2010
DOI: 10.1111/j.1525-1446.2010.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Brand Image for Public Health Nursing

Abstract: Public health nurses (PHNs) have declined as a proportion of both the nursing and the public health workforces in the past 2 decades. This decline comes as 30 states report public health nursing as the sector most affected in the overall public health shortage. Taken together, these data point to a need for renewed recruitment efforts. However, the current public images of nurses are primarily those of professionals employed in hospital settings. Therefore, this paper describes the development of a marketable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This case study confirms one of the major conclusions of the published literature, namely the sources of job satisfaction (Baldwin et al., ; Curtis & Glacken, ; Graham et al., ; Haugh & Laschinger, ; Keller et al., ). It is clear that job satisfaction is an outgrowth of an organizational structure which concentrates on three key issues—the communications between the ranks of the hierarchy `which the organizational structure encourages/discourages, the physical working environment it provides, and the resources it furnishes workers to meet the demands laid on them.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This case study confirms one of the major conclusions of the published literature, namely the sources of job satisfaction (Baldwin et al., ; Curtis & Glacken, ; Graham et al., ; Haugh & Laschinger, ; Keller et al., ). It is clear that job satisfaction is an outgrowth of an organizational structure which concentrates on three key issues—the communications between the ranks of the hierarchy `which the organizational structure encourages/discourages, the physical working environment it provides, and the resources it furnishes workers to meet the demands laid on them.…”
Section: Resultssupporting
confidence: 83%
“…Finally, the Baldwin et al. () study concluded that to improve recruitment to the profession public health nursing needed to be ‘re‐branded’ and given a more defined and coherent public visibility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining the nursing brand have largely relied upon qualitative narratives to describe some form of a consistent nursing image (Baldwin, Lyons, & Issel, 2011; Emeghebo, 2012; Morris, 2007). However, sparse studies exist, which clearly identify and quantitatively measure perceptions of the actual vs desired brand image and brand position for the nursing profession.…”
Section: Background: Review Of the Literaturementioning
confidence: 99%